The Preparedness of Pharmacist in Community Setting to Cope with Globalization Impact - Herman, Max Joseph; Handayani, Rini Sasanti (Jurnal Kefarmasian Indonesia, 2015)
A descriptive study to identify the preparedness of pharmacist in community pharmacies to cope with globalization impact was conducted in 2009. This cross-sectional study was done in DKI Jakarta, Bali and Maluku. Informants were purposively determined involving pharmacists from schools of pharmacy, Indonesian Pharmacist Association (IAI), community pharmacies, Provincial and District Health Offices, as well as comunity pharmacy owners. Primary data were collected through in-depth interviews and observation using check-list in community pharmacy. Data were analyzed descriptively and qualitatively using triangulation method. Results of the study show that according to Health Offices and the Indonesian Pharmacist Association, pharmacists were not adequately prepared and pharmacists in stand alone community pharmacy are less prepared than those in a network or franchise pharmacy. Licensed pharmacists of network community pharmacy in the metropolis are going to prepare themselves to face the new patient-oriented paradigm and to meet the standard of pharmacy service, whereas stand-alone community pharmacy still prioritized fast service and lower drug price